Corte e recortes do turismo no Maciço de Baturité – Ce: reflexões a partir da avaliação do Programa de Apoio ao Turismo Regional (PROATUR) - Porto, Luana Cavalcanti (2008)
Considering the role of tourism financing as an instrument of public policy, the present study consists on the evaluation of the Regional Tourism Support Program (PROATUR) – Brazil´s Northeast Bank (BNB) financing program with resources from Northeast´s Constitutional Fund (FNE) – as a policy of tourism interiorization to Baturité´s Ridge region. To subsidize this proposal, there have been approached themes related to the importance of tourism as an instrument of regional development, the role of financing as a public policy for tourism support and the profile of the sample cities – Baturité, Guaramiranga, Mulungu and Pacoti – where there has been developed a field research to approach the work theme to the reality investigated, through a qualitative research. Under this scope, it has been learnt that the tourism development factor of a locality goes much beyond the credit availability, and must involve the integration of the Region´s municipalities, the orchestration of the federal players and the participation of the local community during tourism planning through a common discussion of the local and state policies to the sustainable development of the activity.